Taḥsīn And Taḥfīz Al-Qur'an Learning Methods: Case Study At Al Furqan Junior High School Jember - Al Ayyubi, Hudzaifah; Mundir, Mundir; Mu'niah, Mu'niah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research departs from the fact that there is still a lot of Al-Qur'an literacy in Indonesia, in line with the need to improve the reading ability of students who graduate from Islamic schools. Likewise with the quality of memorization. The application of the Taḥsīn and Taḥfīz Al-Qur'an learning methods has long been applied at Al Furqan Middle School Jember, but it has never been studied objectively how the advantages & disadvantages of these methods, as well as strategic solutions to produce better student reading and memorization. This research uses a qualitative approach with a case study type. The technique for determining research subjects uses a purposive technique. Data collection techniques through observation, interviews and documentation. Data analysis techniques use interactive model analysis techniques which consist of data reduction, data presentation, and drawing conclusions. The techniques used to test the validity of the data are focused on using triangulation techniques between data sources. The results showed that the taḥsīn & taḥfīz Al-Qur'an learning method used by Al Furqan Junior High School Jember was the Ummi method. The advantages and disadvantages of the method consist of three educational components, namely: the Material side, the Strategy side, and the Management side. Strategic solutions that can be implemented to overcome this shortcoming include: First, from a material standpoint, always learn from other methods and upgrade teachers, as well as provide additional hours for students who are behind on memorization targets. Second, Sisi's strategy, asatidz provides direction for spiritual motivation for students, and there is muroja'ah time between completing the halaqoh opening prayer and before adding to the memorization. Third, the management makes the achievement of students' memorization targets a condition for taking report cards, and the memorization targets are controlled in the Muroja'ah Chart.